2022
DOI: 10.1039/d1ee02889h
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput oxygen chemical potential engineering of perovskite oxides for chemical looping applications

Abstract: Chemical looping (CL) represents a versatile, emerging strategy for sustainable chemical and energy conversion. Designing metal oxide oxygen carriers with suitable redox properties remains one of the most critical challenges...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 118 publications
0
36
0
1
Order By: Relevance
“…The methodology together with the computational details will be published in a separate article. With respect to utilization of first-principles calculations for iron-based oxygen carriers, there have been some previous studies, although the approach of calculating energetics and heat capacities for inclusion in general multicomponent calculations has not been done previously to our knowledge. The focus has been on a few key compounds within the K–Fe–Ti–O phase space, namely, K 0.4 Fe 0.4 Ti 0.6 O 2 , K 0.85 Fe 0.85 Ti 0.15 O 2 , KTi 8 O 16 , and KTi 8 O 16.5 , as well as FeTiO 3 , which was included as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology together with the computational details will be published in a separate article. With respect to utilization of first-principles calculations for iron-based oxygen carriers, there have been some previous studies, although the approach of calculating energetics and heat capacities for inclusion in general multicomponent calculations has not been done previously to our knowledge. The focus has been on a few key compounds within the K–Fe–Ti–O phase space, namely, K 0.4 Fe 0.4 Ti 0.6 O 2 , K 0.85 Fe 0.85 Ti 0.15 O 2 , KTi 8 O 16 , and KTi 8 O 16.5 , as well as FeTiO 3 , which was included as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…As for the optimisation of metal oxides, the use of computational screening of materials could facilitate the search for the ideal metal oxides combination for the proposed technology. 20,21,[97][98][99] A demonstration of this process on a pilot scale at optimum conditions would help bring it closer to practical implementation and provide data for further determining its technical and economic viability for large scale efficient utilisation of CO 2 .…”
Section: Experimental Proof Of Conceptmentioning
confidence: 99%
“…Since the prediction method is only sensitive to parameters such as temperature, and the material category has little influence on it, this method can be widely applied to chemical looping processes and has similar accuracy on various materials under equilibrium or near equilibrium situation. Li et al [154] recently reported the oxygen chemical potentials for over 2000 perovskite oxides were simulated as a function of their oxygen vacancy concentrations and more than 100 materials were predicted to be applicable. Among the potential candidates, intriguingly, "nonobvious".…”
Section: Primary Materials Selectionmentioning
confidence: 99%